Nests and broods of Mexican Duck (Anas diazi) in Penjamo, Guanajuato, Mexico - Pérez Arteaga, Alejandro; Monterrubio Rico, Tiberio; Huacuz Elías, Dolores del Carmen; Herrerías Diego, Yvonne (Acta Universitaria, 2019)
Seven nests of the Mexican Duck (Anas diazi) from Penjamo, Guanajuato, Mexico are described. The nearest nest-to-water body distance ranged from 100 m to 800 m; the nearest distance to standing water ranged from 150 m to 1200 m; the nesting cover was between 50 cm to 130 cm tall. Nests were mostly of a low-cup lateral and well-concealed type. External dimensions ranged from 25 cm to 45 cm × 20 cm to 33 cm, 0 cm to 13 cm tall; internal dimensions ranged from 17 cm to 36 cm × 9 cm to 20 cm. The primary nest material was wheat stubble, and the secondary material was Bouteloua-sorghum. When found, clutches consisted of 1-6 eggs, including viable (n = 2), poached (n = 1), abandoned (n = 2) and successful (n = 1) eggs. Observed broods (n = 6) had between 3 and 9 ducklings found over and up to 400 m from the standing water. Due to the scarcity of available information on the species, these results contribute to its knowledge on the most important distribution area.